Appropriate Methods, Strategies and Techniques for Teaching Arabic Reading Comprehension in Secondary School in Nigeria - Tunde Ahmed Alfabanni (Lembaga Publikasi Ilmiah Universitas Islam Bunga Bangsa Cirebon, 2025)
Arabic, as a foreign language in Nigeria, is predominantly taught within formal school environments where students often face persistent challenges in reading comprehension. These difficulties are largely attributed to the dominance of traditional grammar–translation methods, limited exposure to authentic texts, and reliance on outdated instructional practices. This study critically examines and synthesizes effective teaching methods, instructional strategies, and classroom techniques that can enhance Arabic reading comprehension in Nigerian secondary schools, where Arabic is neither a native nor widely spoken language. Adopting a conceptual and literature-based approach, the research analyses scholarly publications, curriculum documents, and relevant educational theories on Arabic instruction in non-Arabic-speaking contexts. The findings indicate that a hybrid model—combining the Direct Method and the Reading Method, reinforced by explicit strategy instruction (e.g., summarisation, questioning, re-reading) and practical techniques (e.g., reading aloud, visual aids, technology integration)—can significantly improve comprehension outcomes, vocabulary acquisition, critical thinking, and learner motivation. The study concludes that contextually responsive integration of method, strategy, and technique offers a transformative framework for Arabic reading instruction in Nigeria. This contribution provides an adaptable instructional model for teachers and serves as a valuable reference for curriculum developers and policymakers in language education reform.